Toward a transdiagnostic tool to evaluate depressive symptoms across mental disorders: Validation of the Calgary depression rating scale in patients with major depressive disorder. (October 2018) - Micoulaud-Franchi, Jean-Arthur; Faugere, Mélanie; Weibel, Sebastien; Faget, Catherine; Lancon, Christophe; Richieri, Raphaëlle; Cermolacce, Michel
Highlights: The Calgary Depression Rating Scale (CDSS) evaluate depressive symptoms. The CDSS is validated in patients with Schizophrenia. The CDSS is validated in patients with major depressive disorder. The CDSS can be used according to a transdiagnostic approach. Abstract: The severity of depressive symptoms across two discrete mental disorders should be evaluated with the same psychometrically validated tools. In patients with schizophrenia the Calgary Depression Rating Scale (CDSS) is recommended for evaluating depressive symptoms. The aim of this study was to validate the CDSS in patients with major depressive disorder. The CDSS exhibit satisfactory psychometric properties for evaluating depressive symptoms in major depressive disorder. Clinicians and researchers now have a validated scale at their disposal to evaluate depressive symptoms in various mental disorders using a transdiagnostic approach.